2017
DOI: 10.1039/c6ra27436f
|View full text |Cite
|
Sign up to set email alerts
|

Influence of removing PMMA residues on surface of CVD graphene using a contact-mode atomic force microscope

Abstract: AFM cleaning technique can be a potential tool to clean the surface defects of 2D materials like TMDs, as well as graphene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 39 publications
6
65
1
Order By: Relevance
“…Therefore, there have been many efforts to remove these PMMA residues by various techniques, among which thermal annealing in vacuum or inert gases are most widely applied. Nonetheless it has been reported that some PMMA residues still remain on the surface after thermal annealing, resulting in scattering and defects .…”
Section: Summary Of Test Results Of Electrical Characterization On Gfmentioning
confidence: 99%
“…Therefore, there have been many efforts to remove these PMMA residues by various techniques, among which thermal annealing in vacuum or inert gases are most widely applied. Nonetheless it has been reported that some PMMA residues still remain on the surface after thermal annealing, resulting in scattering and defects .…”
Section: Summary Of Test Results Of Electrical Characterization On Gfmentioning
confidence: 99%
“…In contrast to the chemical and thermal approaches described above, a mechanical approach is to use an AFM tip to “sweep” the polymer residue off the surface in contact mode. This AFM cleaning method induces no chemical reactions, has no restriction on the type of 2D crystal, and can retain the original 2D crystal thickness and surface roughness . It has been applied to both exfoliated and CVD‐grown graphene on various substrates, and the carrier mobility of graphene after the cleaning was reported to increase by 20% compared to before cleaning .…”
Section: Introductionmentioning
confidence: 99%
“…While several studies have used the AFM contact‐mode‐cleaning technique on graphene and reported transfer characteristics and Hall resistance measurements, to our knowledge there are no similar reports on TMDs. More specifically, there is no report on the impact of polymer reside on the electrical performance of EDL‐gated TMDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall prediction, in the case of suspended graphene, is that the doping effects should be small and strongly dependent on molecule orientation. [49][50][51] Adv. [22] They predicted a very different doping behavior, as compared to suspended graphene: for defective SiO 2 substrates, adsorbed water molecules shift and couple the substrate's impurity bands with graphene bands, leading to much stronger (hole-type) doping, as compared to suspended graphene.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%